Cerebral Ketone Body Oxidation Is Facilitated by a High Fat Diet Enriched with Advanced Glycation End Products in Normal and Diabetic Rats - de Assis, Adriano M.; da Silva, Jussemara S.; Rech, Anderson; Longoni, Aline; Nonose, Yasmine; Repond, Cendrine; de Bittencourt Pasquali, Matheus A.; Moreira, José C. F.; Souza, Diogo O.; Pellerin, Luc (Frontiers in Neuroscience, 2016)
Diabetes mellitus (DM) causes important modifications in the availability and use of different energy substrates in various organs and tissues. Similarly, dietary manipulations such as high fat diets also affect systemic energy metabolism. However, how the brain adapts to these situations remains unclear. To investigate these issues, control and alloxan-induced type I diabetic rats were fed either a standard or a high fat diet enriched with advanced glycation end products (AGEs) (HAGE diet). The HAGE diet increased their levels of blood ketone bodies, and this effect was exacerbated by DM induction. To determine the effects of diet and/or DM induction on key cerebral bioenergetic parameters, both ketone bodies (β-hydroxybutyric acid) and lactate oxidation were measured. In parallel, the expression of Monocarboxylate Transporter 1 (MCT1) and 2 (MCT2) isoforms in hippocampal and cortical slices from rats submitted to these diets was assessed. Ketone body oxidation increased while lactate oxidation decreased in hippocampal and cortical slices in both control and diabetic rats fed a HAGE diet. In parallel, the expression of both MCT1 and MCT2 increased only in the cerebral cortex in diabetic rats fed a HAGE diet. These results suggest that a shift in the preferential cerebral energy substrate utilization in favor of ketone bodies in animals fed a HAGE diet, an effect that, in DM animals, is accompanied by the enhanced expression of the related transporters.